The 'respect rather than resect' principle in mitral valve repair: the lateral dislocation of the P2 technique. Issue 9 (September 2017) - Zanobini, Marco; Ricciardi, Gabriella; Mammana, Francesco Liborio; Kassem, Samer; Poggio, Paolo; Di Minno, Alessandro; Cavallotti, L.; Saccocci, Matteo
Abstract : Background: Leaflet resection represents the reference standard for surgical treatment of mitral valve (MV) regurgitation. New approaches recently1 proposed place emphasis on respecting, rather than resecting, the leaflet tissue to avoid the drawbacks of the 'resection' approach. Objectives: The lateral dislocation of mid portion of mitral posterior leaflet (P2) technique for MV repair is a nonresectional technique in which the prolapsed P2 segment is sutured to normal P1 segment. Our study evaluates the effectiveness of this technique. Patients and methods: We performed the procedure on seven patients. Once ring annular sutures were placed, the prolapsed P2 segment was dislocated toward the normal P1 segment with a rotation of 90° and without any resection. If present, residual clefts between P2 and P3 segments were closed. Once the absence of residual mitral regurgitation is confirmed by saline pressure test, ring annuloplasty was completed. The valve was evaluated using transesophageal echocardiography in the operating room and by transthoracic echocardiography before discharge. Results: At the last follow-up visit, transthoracic echocardiography revealed no mitral regurgitation and normal TRANSVALVULAR gradients. Conclusion: The lateral dislocation of P2 is an easily fine-tuned technique for isolated P2 prolapse, with the advantage of short aortic cross-clamp and cardiopulmonary bypass times. We think it might be very favorable in older and frail patients. Long-term follow-up is necessary to assess the durability of this technique.